SYST-13 PHASE II STUDY OF THE COMBINATION OF LIPOSOMAL IRINOTECAN AND PEMBROLIZUMAB FOR TRIPLE-NEGATIVE BREAST CANCER (TNBC) WITH BRAIN METASTASES (BM). (5th August 2022) - Xi, Jing; Luo, Jingqing; O'Sullivan, Ciara; Chen, Nan; Stringer-Reasor, Erica; Ma, Cynthia; Campian, Jian
Abstract: BACKGROUND: Breast cancer is one of the most common cancers associated with brain metastases (BM). Up to 50% of patients with metastatic triple-negative breast cancer (TNBC) develop BM which portends a poor prognosis, with a median survival of 4.4-7.3 months. There is a lack of effective systemic therapy. Irinotecan is a topoisomerase-1 inhibitor with a response rate of 5-23% in advanced breast cancer. Nal-IRI is an intravenous liposomal formulation of irinotecan, with greater efficacy in tumor growth inhibition and the ability to cross the blood brain barrier (BBB) than irinotecan, resulting in a prolonged survival in preclinical TNBC BM models. Additionally, Nal-IRI has demonstrated promising anti-tumor activity in patients with TNBC- BM in a phase-I trial (NCT01770353). Pembrolizumab is a humanized anti-PD-1 monoclonal antibody which has shown efficacy in TNBC. The purpose of this study is to evaluate whether the combination of Nal-IRI and pembrolizumab can provide a synergic effect to control the CNS disease and prolong survival in TNBC with progressive BM. METHODS: This is a phase II, single arm trial with a safety lead-in to evaluate the efficacy of nal-IRI (50-70mg/m2 IV Q2W) in combination with pembrolizumab (400mg IV Q6W). Simon's 2-stage design is used, with 18 patients in the 1st stage and additional 24 at 2nd stage for a total of 42. The first 6 patients will serve as a safety lead-in. Key eligibilities include: histologically/cytologically confirmed TNBC with new or progressive BM; prior immunotherapy is allowed but not prior nal-IRI/irinotecan; prior sacituzumab-govitecan is permitted if disease stable for ≥16-week while on therapy and ≥24-week washout prior to starting trial; measurable disease; and ≤4 prior lines of therapy in the metastatic setting. The primary endpoint is CNS disease control rate (DCR) at 6 months using RANO-BM criteria. Secondary endpoints include CNS and non-CNS ORR, PFS and OS. (ClinicalTrials.gov: NCT05255666)